Teacher Development vs Teacher Training in the EFL/ ESL Class and the ICTs’ role - Papadaki, Aggeliki; Karagianni, Eleni; Driga, Anna Maria (Eximia, 2023)
The aim of the article is to present critically some concepts in teacher development in ELT. In the first part, there is a brief discussion of terms, such as Teacher Development, Training, the three Teacher Education Models, the three conceptions of teaching, the four elements of teaching training courses, the Enriched Reflection Model and the integration of theory and practice in training courses. In the second part, there is a description of the training context of a particular course, while its content and the processes followed are analyzed and evaluated. Finally, there is a brief discussion around these ideas.